1987
DOI: 10.1017/s0031182000057644
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola hepatica in vitro: increased susceptibility to fasciolicides in a defined serum-free medium

Abstract: The cidal properties of some phenolic, halogenated diphenyl, salicylanilide, benzimidazole and diaminophenoxyalkane anthelmintics, against 6-week-old worms of Fasciola hepatica were assessed in vitro. In a conventional fluke culture medium containing RPMI 1640, supplemented with serum with or without rabbit erythrocytes or pink-ghosts, only the halogenated diphenyl and salicylanilide compounds showed activity at concentrations equal to or less than 100 microM. However, when basal, serum and cell-free RPMI 1640… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In the present study, in vitro secretion was found to be increased in the presence of FCS or BSA. However, it should be noted that chemical and physical characteristics of the culture medium can influence the in vitro drug activity (Jenkins et al, 1980;Rosenfeld and Laubach, 1986;Jenkins et al, 1987); in the present case, some drugs could bind to serum proteins becoming less available to the worms. Given this possibility, the worms were always exposed to the drugs in supplement-free medium, and medium with BSA was only used to study the secretion post-drug-treatment.…”
Section: Discussionmentioning
confidence: 87%
“…In the present study, in vitro secretion was found to be increased in the presence of FCS or BSA. However, it should be noted that chemical and physical characteristics of the culture medium can influence the in vitro drug activity (Jenkins et al, 1980;Rosenfeld and Laubach, 1986;Jenkins et al, 1987); in the present case, some drugs could bind to serum proteins becoming less available to the worms. Given this possibility, the worms were always exposed to the drugs in supplement-free medium, and medium with BSA was only used to study the secretion post-drug-treatment.…”
Section: Discussionmentioning
confidence: 87%
“…A similar observation was made in a previous study, which evaluated the fasciocidal properties of phenolic, halogenated diphenyl, salicylanilide, benzimidazole and diaminophenoxyalkane anthelmintics in serum-free and serum-supplemented media. 17 The increased potency of the fasciolicides in the absence of serum has been explained by drug serum protein binding, which renders the drugs less accessible to the flukes. 17 In conclusion, we have presented the first evidence of the potent fasciocidal properties of a 1,2,4-trioxolane and this is supported by in vivo and in vitro studies and underscored by SEM observations.…”
Section: Discussionmentioning
confidence: 99%
“…17 The increased potency of the fasciolicides in the absence of serum has been explained by drug serum protein binding, which renders the drugs less accessible to the flukes. 17 In conclusion, we have presented the first evidence of the potent fasciocidal properties of a 1,2,4-trioxolane and this is supported by in vivo and in vitro studies and underscored by SEM observations. Our results call for additional studies in larger mammals, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…New compounds are now tested in our laboratory under both sets of conditions which in some instances provides useful additional information about their properties. The use of metabolizing agents such as the inclusion of rabbit liver microsomes to the culture system (JENKINS et al, 1987) may further improve the evaluation of some types of compound.…”
Section: Discussionmentioning
confidence: 99%